Electron Microscopic Retina Changes in Rabbit Eyes with Perfluorocarbon Liquids Intravitreal Tamponade - G. M. Arslanov; B. M. Aznabaev; T. R. Mukhamadeev; Z. R. Yanbukhtina; T. I. Dibaev; G. R. Shakirova (Oftalʹmologiâ, 2019)
Purpose. Analysis of electron microscopic changes in rabbit eyes with intravitreal tamponade of perfluorocarbon liquids (PFCL) (perfluoro-1,3-dimethylcyclohexane and perfluorodecalin). Material and Methods. The study was performed on Chinchilla breed rabbits. 25G vitrectomy with PFCL intravitreal tamponade was performed on 12 eyes of 6 rabbits (perfluorodecalin (Bausch+Lomb «Dk-line», USA) and perfluoro-1,3-dimethylcyclohexane (ZAO “Optimedservis”, Russia). Standard three-port vitrectomy technique was used. After removal of the vitreous body 2.5 ml of PFCL were injected in vitreous cavity. Research studies were performed in 5, 14 and 30 days after surgery by electron microscopy. Eyes were enucleated in 20 minutes after animal was killed by air embolization. Intact eyes were used as a control. All samples were prepared in same conditions. The damage of the retina architectonics and the presence of intracellular inclusions were evaluated. Results. Tamponade of the vitreous cavity by both types of PFCL in 5, 14 and 30 day caused following similar electron microscopic changes at date: swelling ganglion layer and dystrophy of inner and outer nuclear layer. Electron microscopic changes in outer nuclear layer appeared at 30 days. The photoreceptor neurons were characterized by single ultrastructural changes. Retina pigment epithelium cells had a typical ultrastructure. Conclusion. Intravitreal perfluoro-1,3-dimethylcyclohexane tamponade caused similar electron microscopic changes as well as perfluorodecalin in the experiment and it was relatively harmless to rabbit retina for up to 14 days. Irreversible changes in the retinal ultrastructure were not observed.